Relationships between Serum Levels of Atazanavir and Renal Toxicity or Lithiasis - C. I. Marinescu; M. Leyes; M. A. Ribas; M. Peñaranda; J. Murillas; A. A. Campins; L. Martin-Pena; B. Barcelo; C. Barceló-Campomar; F. Grases; G. Frontera; Melchor Riera Jaume (AIDS Research and Treatment)
The main aim of this study is to describe the relationship between serum levels of atazanavir, renal toxicity, and lithiasis. This is a prospective observational study of patients being treated with atazanavir (ATV) at Son Espases Teaching Hospital, Palma de Mallorca, between 2011 and 2013. The study includes 98 patients. Sixteen were found to have a history of urolithiasis. During a median monitoring period of 23 months, nine patients suffered renal colic, in three of whom ATV crystals were evidenced in urine. Cumulative incidence of renal colic was 9.2 per 100 patients. The variables related to having renal colic were the presence of alkaline urine pH and lower basal creatinine clearance. The mean serum level of ATV was slightly higher in patients with renal colic—1,303 μg/L versus 1,161 μg/L—but did not reach statistical significance. Neither were any significant differences detected by analysing the levels according to the timetable for ATV dosage. Cumulative incidence of renal colic was high in patients being treated with ATV, in 33% of whom the presence of ATV crystals was evidenced in urine. We were unable to demonstrate a relationship between ATV serum levels and renal colic or progression towards renal failure.